2014
DOI: 10.1161/strokeaha.113.003200
|View full text |Cite
|
Sign up to set email alerts
|

Hemicraniectomy and Durotomy Upon Deterioration From Infarction-Related Swelling Trial

Abstract: Background and Purpose HeADDFIRST was a randomized pilot study to obtain information necessary to design a Phase III trial to evaluate the benefit of surgical decompression for brain swelling from large supratentorial cerebral hemispheric infarction (LSCHI). Methods All stroke patients were screened for eligibility [age 18–75, NIHSS ≥ 18 with Item 1a < 2 (responsive to minor stimulation), and CT demonstrating unilateral, complete MCA territory infarction by specific imaging criteria]. All enrolled patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
107
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(117 citation statements)
references
References 11 publications
1
107
0
4
Order By: Relevance
“…8,11,14,30,31 Its beneficial effects may vary among patients. In this study, we set out to identify risk factors that can be associated with increased mortality rate and poor outcome after surgery and aid the patient selection for DH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,11,14,30,31 Its beneficial effects may vary among patients. In this study, we set out to identify risk factors that can be associated with increased mortality rate and poor outcome after surgery and aid the patient selection for DH.…”
Section: Discussionmentioning
confidence: 99%
“…8 Vahedi et al conducted a pooled analysis of the major trials and reported that 43% of patients in the decompressive surgery group had an mRS score of ≤ 3 (compared with 21% who received medical management), and the mortality rate was 22% (compared with 71%). 30 The ages of patients who underwent DH ranged from 22 to 82 in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…We could have expanded the number of eligible patients by including DC trials that enrolled patients past 48 hours; however, there is sufficient evidence to suggest that patients treated later experience a different clinical course. 5,26 We prespecified exclusion of patients undergoing late DC in order to maintain a pure sample population, which is reflected in the consistency of treatment effect across our studies as calculated by I 2 . For similar reasons, we excluded nonrandomized trials, whose results are potentially subject to substantial bias.…”
Section: Discussionmentioning
confidence: 99%
“…5,10,11,[23][24][25] One study was excluded, Hemicraniectomy and Durotomy Upon Deterioration From Infarction-Related Swelling Trial (HeADDFIRST), which enrolled patients up to 96 hours from onset and, notably, intentionally delayed DC until patients had severe clinical or radiographic deterioration. 26 Inclusion criteria for the individual trials were similar, with exception of the prespecified age ranges (table). Baseline patient characteristics of the treatment groups were well-matched with exception of Jüttler et al 25 and Slezins et al, 23 which reported higher mean NIH Stroke Scale scores in the medically managed group.…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%
“…However, a quick inquiry in the TABNET database system disclosed that, from January 2008 to December 2014, a total of 3,753 acute stroke patients were admitted at that institution 3 . If those numbers hold true, they suggest that Brazilian patients might be less than half as likely to receive DC than their counterparts in the HeADDFIRST trial, a significant difference (eligibility rate 0.53% vs 1.35%; OR 0.39, 95%CI 0.23-0.64; p = 0.0002) 4 . Key to understanding this conundrum -and definitely more important than statistics -is why patients are being declined surgery.…”
mentioning
confidence: 99%